Wild and trapped: a history of Colombian zoos and its revelations of animal fortunes and State entanglements, 1930s-1990s - Claudia Leal (História, Ciências, Saúde: Manguinhos)
Abstract This article presents the first history of Colombian zoos and one of the few contributions to the history of these institutions in Latin America. It proposes that in this region’s zoos native animals tended to predominate, signaling the increasing transformation of forests and other native ecosystems into croplands and pasturelands, as well as the growing distance between people and natural environments. Colombian zoos additionally underscore the limitations of the State in its period of most rapid expansion. They reveal how private interests overshadowed the State by providing public amenities, but also how they offered unconventional solutions to certain hurdles of State formation.